A Dual-Function Instantaneous Power Theory for Operation of Three-Level Neutral-Point-Clamped Inverter-Based Shunt Active Power Filter - Yap Hoon; Mohd Amran Mohd Radzi; Mohd Khair Hassan; Nashiren Farzilah Mailah (Energies, 2018)
This paper proposes a simple yet effective reference current generation algorithm based on instantaneous power pq theory to enhance mitigation performance of a three-phase three-level neutral-point-clamped (NPC) inverter-based shunt active power filter (SAPF). The proposed algorithm is developed for dual functionality: generate reference current and synchronization phase to effectively govern operation of SAPF in mitigating harmonic current and compensating reactive power. Three key modifications are implemented: (1) replacement of numerical low-pass filter (LPF) with an average power detector to improve mitigation performance; (2) removal of needless reactive element to reduce algorithm complexity; and (3) integration of phase tracking feature to eliminate the needs of phase-locked loop (PLL). Simulation work of SAPF with the proposed algorithm was conducted and assessed in MATLAB–Simulink. In addition, to verify feasibility of the proposed algorithm, a laboratory prototype as constructed with TMS320F28335 digital signal processor (DSP) programmed as the controller. Performance of SAPF achieved by utilizing the proposed algorithm was thoroughly investigated and benchmarked with that demonstrated using the existing pq theory algorithm to evaluate the inherent advantages. Simulation and experimental results are obtained for different nonlinear loads and test conditions. Responses demonstrated by SAPF in both simulation and experimental works reveal superiority of the proposed algorithm over the existing algorithm.